Якісний аналіз пептидного та білкового складу цитозольних фракцій фетальних тканин людини - Черкашина, Д.В.; Семенченко, О.Ю.; Петренко, О.Ю. (Ukrainica Bioorganica Acta; 2008; 6(1): 23-27, 2008)
Проведено препаративний розподіл тотального цитозоля фетальних тканин людини (мезенхімально-мезодермального походження) шляхом хроматографії у полівініловому гелі та горизонтального ультратонкого електрофорезу на поліакриламідному гелі. Під час хроматографії було отримано 6 фракцій, одна з яких білкова, 5 – пептидні. При електрофоретичному розподілі білків було одержано 13-15 білкових фракцій з молекулярною масою від 9 до 110 кДа *************************************************************************************************** Actual problem of present-day stem and progenitor cell biology and regenerative medicine is a search of biologically active substances in tissues enriched by stem/progenitor cells. Area of our interest is the fetal tissues mainly of mesenchymal and mesodermal origin that demonstrated a wide spectrum of biological activity. In this study low molecular weight peptides and proteins of human fetal tissue cytosol (FTC) obtained by two-steps high-speed ultracentrifugation of tissue homogenate was analyzed by gel-chromatography and gel-electrophoresis. Gel-chromatography was performed using polyvinyl gels TSK-Gel Toyopearl HW-40, HW-60 Fine (Toyosoda, Japan) and tris-HCl buffer (25 mM, pH 7.5) contained 1M urea and 100 mM NaCl as an eluent. Obtained fractions were estimated spectrophotometrically, wave-length 254 and 280 nm. Horizontal ultrathin gel-electrophoresis was performed using polyacrylamide gel with pore gradient 4-22.5%. Sodium dodecyl sulfate was used as a main detergent. During gel-chromatography 6 pronounced peaks were obtained. One of them was a protein fraction, the rest 5 – peptide ones with molecular weights 2990, 2410, 1570, 1150, 900 Da approximately. Protein fraction was about 34000 Da. After gel-electrophoresis of total FTC 13 protein fractions were discovered. Two of them fit with standards – chemotrypsinogen A and albumin. For protein fraction obtained during chromatographic separation 15 lines were shown, 3 of them fit with standards, additional one was cytochrome c. Protein molecular weight range was between 9000 and 110000 Da.
Qualitative analysis of peptid and protein composition of human fetal tissue cytosolic fractions
Черкашина Д.В., Семенченко О.Ю., Петренко О.Ю. Якісний аналіз пептидного та білкового складу цитозольних фракцій фетальних тканин людини. Ukrainica Bioorganica Acta; 2008; 6(1): 23-27
Keywords: фетальні тканини; гель-хроматографія; горизонтальний ультратонкий гель-електрофорез; біорегулятори стовбурових та прогеніторних клітин